Pengaruh Minuman Berwarna dan Minuman Berwarna Berkarbonasi Terhadap Perubahan Warna Resin Komposit Nanohybrid - Imam Hidayatsyah; Lendrawati Lendrawati; Reni Nofika (Faculty of Dentistry Universitas Andalas, 2020)
Introduction: resin composites have solubility and water sorption properties. Resin composites can get discoloration due to intrinsic and extrinsic factors. The purpose of this research is to know the effect of colored drinks and carbonated colored drinks on nanohybrid resin composite discoloration. Material and Method: This research was true experimental research with post test only group design. The samples used were 32 pieces of resin composites nanohybrid in disc-shaped with 6mm in diameters and 2mm in thickness, lighted by LED for 20 seconds. Samples were divided into groups immersed in colored drinks and groups immersed in carbonated colored drinks. The discoloration measurement used spectrophotometer UV-Visible by assess absorbance value. Results: the results showed that the group immersed in colored drinks has average absorbance value as big as 0,109 and the group immersed in carbonated colored drinks has average absorbance value as big as 0,175. the results of independent sample test showed a significant difference with a p value 0,001. Conclusion: Carbonated colored drinks have a greater influence on the color change of nanohybrid resin composites than colored drinks because carbonated colored drinks have more acidic properties.